Corporate Taxes and Financing Methods for Taxable Acquisitions* - DHALIWAL, DAN S.; NEWBERRY, KAYE J.; WEAVER, CONNIE D. (Contemporary Accounting Research, 2005)
Abstract We examine the influence of corporate taxes on U.S. firms' financing methods for taxable acquisitions of 100 percent of a target corporation's stock. We conduct tests of acquirer firms' use of debt or internal funds as the funding source for these acquisitions over the period 1987‐97. Our results provide the first empirical evidence that U.S. firms' use of debt to fund acquisitions significantly declines as foreign tax credit limitations reduce the marginal tax benefits received from borrowing. This finding is consistent with earlier speculation that U.S. foreign tax credit provisions could materially affect the capital costs of U.S. companies in debt‐financed acquisitions. We also find that these firms are generally high‐tax‐rate corporations whose financing choices are not significantly influenced by whether they acquire target‐firm tax loss carryovers. Our findings contribute to the accounting literature on the influence of taxes on the structure and financing of corporate acquisitions.